P635 Risankizumab - real world Israeli data in severe refractory IBD patients. (30th January 2023) - Bar-Gil Shitrit, A; Gil, Y; Israeli, E; Koslowsky, B; Mazuz, B; Israel, I; Goldenberg, R; Ben-Bassat, O; Weisbrud, A; Ledder, O; Zinger, A; Ben Horin, S; et al.
Abstract: Background: The landscape of inflammatory bowel disease (IBD) treatment is rapidly expanding with the development of new therapeutic options. Risankizumab (Skyrizi®), a humanised IgG monoclonal antibody that targets the p19 subunit of IL-23, was developed for the treatment of immunological and inflammatory disorders, and recently began to be investigated also in the field of IBD. Most patients who receive Risankizumab do so as part of clinical trials, but there are a number of patients with severe refractory disease who have received it as a compassion treatment and they present preliminary Real-World data for this drug. Aim: to present the real-world data of patients with severe refractory IBD who received Risankizumab as a compassion treatment. Methods: Retrospective Israeli multicenter study from 6 tertiary IBD centers (Shaare Zedek medical center, Wolfson, Ichilov, Hadassah, Sheba and Barzilai ) on 21 patients with severe refractory IBD (18 CD, 3 UC) who received Risankizumab (IV 600 mg at 0, 4, 8 weeks; then SC 180 or 360 mg SC every 8 weeks) as compassionate treatment with a median follow up of 30 weeks (4-52 weeks). Results: Although some of the clinical and laboratory parameters are still being collected, we can present some trends. 21 patients were included in the analysis. 17 /21 were after ustekinumab failure. At week 12, there was a significant reduction in Harvey-Bradshaw index (HBI) for Crohn's disease, in CRP values and Calprotectin as compared with the baseline data (10.13 to 4.82, p=0.03; 4.16 to 1.62, p=0.004; 3758 to 961, p=0.02, Respectively). In addition, there was a reduction in the percentage of steroids dependent patients (0.44 to 0.14, p=0.07). In the margins of the study, it is worth noting that particularly patients with difficult and resistant disease, who were TPN dependent or on the verge of surgery, as a result of treatment were weaned from TPN or were able to avoid surgery. Conclusion: According to real-world data, Risankizumab holds a great therapeutic promise even for patients with particularly serious and resistant diseases.